2015
DOI: 10.1002/ajmg.b.32340
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine receptor DRD4 gene and stressful life events in persistent attention deficit hyperactivity disorder

Abstract: We performed a case-control association study in persistent ADHD considering eight candidate genes (DRD4, DAT1/ SLC6A3, COMT, ADRA2A, CES1, CYP2D6, LPHN3, and OPRM1) and found additional evidence for the involvement of the Dup 120bp and VNTR 48bp functional variants within the dopamine receptor DRD4 gene in the etiology of adult ADHD. We subsequently investigated the interaction of stressful life events with these two DRD4 polymorphisms, and the impact of such events on the severity of ADHD symptomatology. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 106 publications
1
12
0
1
Order By: Relevance
“…The 7R polymorphism has been proposed as one of the genetic risk factors for ADHD (22). In line with the current findings, Sánchez-Mora et al (54) had already demonstrated that the effect of the number of stressful life events on inattention scores was stronger among 7R-non-carriers than 7R-carriers. Note however, that ratings by others are needed to exclude the possibility that 7R-carriers and 7R-non-carriers report their inattention differently.…”
Section: Discussionsupporting
confidence: 90%
“…The 7R polymorphism has been proposed as one of the genetic risk factors for ADHD (22). In line with the current findings, Sánchez-Mora et al (54) had already demonstrated that the effect of the number of stressful life events on inattention scores was stronger among 7R-non-carriers than 7R-carriers. Note however, that ratings by others are needed to exclude the possibility that 7R-carriers and 7R-non-carriers report their inattention differently.…”
Section: Discussionsupporting
confidence: 90%
“…Family-based designs are robust against population admixture and stratification, and allow conducting complex segregation analysis and linkage and association studies that would be next to impossible in case/control-based designs [32,61,62,63]. With few exceptions [64,65,66,67], recent genetic studies on ADHD have primarily focused on case/control-based designs to study genetic contributions to ADHD susceptibility [15,16,18,68,69,70].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the last 4.5 years of the literature included 34 studies that focused on ADHD diagnosis and related symptoms. A majority of studies focused their environmental exposure on related to psychosocial [67][68][69][70][71][72][73][74][75][76][77], stress and adversity [27,75,[77][78][79][80][81][82][83][84], and trauma-related exposures [85]. Very few focused on toxicant exposure such as blood lead levels [86, 87••, 88], phthalate metabolites [89], and organophosphate pesticide exposure [90].…”
Section: Attention Deficit Hyperactivity Disordermentioning
confidence: 99%